Non-NMDA-Type Glutamate Receptors Are Essential for Maturation But Not for Initial Assembly of Synapses at Drosophila Neuromuscular Junctions - Schmid, Andreas (J Neurosci, 2006)
The assembly of glutamatergic postsynaptic densities (PSDs) seems to involve the gradual recruitment of molecular components from diffuse cellular pools. Whether the glutamate receptors themselves are needed to instruct the structural and molecular assembly of the PSD has hardly been addressed. Here, we engineered Drosophila neuromuscular junctions (NMJs) to express none or only drastically reduced amounts of their postsynaptic non-NMDA-type glutamate receptors. At such NMJs, principal synapse formation proceeded and presynaptic active zones showed normal composition and ultrastructure as well as proper glutamate release. At the postsynaptic site, initial steps of molecular and structural assembly took place as well. However, growth of the nascent PSDs to mature size was inhibited, and proteins normally excluded from PSD membranes remained at these apparently immature sites. Intriguingly, synaptic transmission as well as glutamate binding to glutamate receptors appeared dispensable for synapse maturation. Thus, our data suggest that incorporation of non-NMDA-type glutamate receptors and likely their protein–protein interactions with additional PSD components triggers a conversion from an initial to a mature stage of PSD assembly.